Work related and individual predictors for incident neck pain among office employees working with video display units. - Korhonen T; Ketola R; Toivonen R; Luukkonen R; Häkkänen M; Viikari-Juntura E; Korhonen, T; Ketola, R; Toivonen, R; Luukkonen, R; Häkkänen, M; Viikari-Juntura, E (Occupational & Environmental Medicine, 2003)
Aims: To investigate work related and individual factors as predictors for incident neck pain among office employees working with video display units (VDUs).Methods: Employees in three administrative units of a medium sized city in Finland (n = 515) received mailed questionnaires in the baseline survey in 1998 and in the follow up survey in 1999. Response rate for the baseline was 81% (n = 416); respondents who reported neck pain for less than eight days during the preceding 12 months were included into the study cohort as healthy subjects (n = 232). The follow up questionnaire 12 months later was completed by 78% (n = 180). Incident neck cases were those reporting neck pain for at least eight days during the preceding 12 months.Results: The annual incidence of neck pain was 34.4% (95% CI 25.5 to 41.3). Poor physical work environment and poor placement of the keyboard increased the risk of neck pain. Among the individual factors, female sex was a strong predictor. Smoking showed a tendency for an increased risk of neck pain. There was an interaction between mental stress and physical exercise, those with higher mental stress and less physical exercise having especially high risk.Conclusion: In the prevention of neck disorders in office work with a high frequency of VDU tasks, attention should be given to the work environment in general and to the more specific aspects of VDU workstation layout. Physical exercise may prevent neck disorders among sedentary employees.